Influence of pruning and the climatic conditions on acorn production in holm oak (Quercus ilex L.) dehesas in SW Spain - Alejano, R; TAPIAS, R; Fernández, M; Torres, Enrique; Alaejos, Joaquín; Domingo, Juan (Annals of Forest Science, 2008)
Acorn production by Quercus ilex L. ssp. ballota (Desf.) Samp. in SW Spain was assessed, and variations between years and the inﬂuence of pruning on it were examined. To this end, an experimental study was conducted at two diﬀerent sites (Calañas and San Bartolomé, in the province of Huelva) where trees were subjected to traditional (light, moderate or heavy) pruning and also to a new (crown-regeneration) pruning method. Acorn yield was quantiﬁed over a period of 5 years in the Calañas plot and 4 in the San Bartolomé plot, and found to average at 95.61 ± 0.76 g DM/m2 , which is equivalent to 6.5 ± 0.05 kg DM/tree; however, yield ﬁgures varied markedly between years depending on the particular climatic conditions. The average acorn production was correlated with the water potential in mid summer (end of July); the annual, spring and autumn rainfall; and the actual evapotranspiration for the period from September (previous year) to August. No signiﬁcant diﬀerences in acorn production between traditional pruning intensities were detected; in fact, there were only hints that heavy pruning might result in decreased acorn yields. The new pruning method used, crown-regeneration, seems promising with a view to increasing acorn yield; however, it should be tested on larger sample sizes before any ﬁnal conclusions can be drawn in this respect. Based on the results, the present health status of holm oaks in southwestern Spain (a result of sustained decline) and the low value of ﬁrewood – which used to be a very important source of income from pruning a few decades ago –, the authors recommend reducing the frequency and intensity of pruning in the dehesas of the study area.
Keywords: acorn production; Holm oak; Masting; pruning